Developmental Care Contributes to Increasing Parent’s Satisfaction - Ika Permanasari; Yeni Rustina; Allenidekania Allenidekania (STRADA : Jurnal Ilmiah Kesehatan, 2021)
A premature infant born with several health problems caused parents anxiety and stress. Developmental care was nursing care based on the infant’s neurodevelopment needs and family support. Qualified nursing care by implementing developmental care can be accessed through parent satisfaction of premature. This study aimed to recognize the relationship of developmental care implementation perceived by nurses with parent’s satisfaction of premature infants. This quantitative study used a cross-sectional design. The sample included 52 neonatal nurses and parents of premature infants used the consecutive sampling method. Data were collected using a questioner and analyzed using person correlation. The analysis results showed that there was a significant relationship between developmental care implementation with parent’s satisfaction of premature infants (p value=0,001). The implementation of developmental care to premature infants can improve the quality of care and increase parent’s satisfaction.